(untitled) (Experimental biology, 2015)
This article presents a result of the introduction to the culture of anthers and isolated microspores of rapeseed with using varieties and hybrids of the first generation. Provides data of the cytological analysis of male gametogenesis, optimize sterilization flower buds, cultivation mediums for the culture of anthers, induction of morphogenesis and regeneration and doubled haploid chromosome number of regenerated. Optimal medium for the induction of embryogenic callus is Gamborg B5 medium (sucrose 90g / l, 66 mg / l of iron chelate, 2.4D – 0.5 mg / l, NAA – 0.25 mg / l). The best result for the induction of embryogenic callus was obtained in sorts Vale 310, SariGol, Hyola 504 Hyola 308. A preliminary field evaluation on phenological characteristics and yield characteristics and oil content derived doubled haploid rape.